Clinical implications of mitral valve geometric alterations in children with dilated cardiomyopathy. (28th December 2015) - Hayashi, Taiyu; Inuzuka, Ryo; Shindo, Takahiro; Ono, Hiroshi; Kaneko, Yukihiro; Kato, Hitoshi
Abstract: We aimed to elucidate the relationship between severity of secondary mitral regurgitation and mitral valve geometry in children with dilated cardiomyopathy. The medical records of 16 children with dilated cardiomyopathy (median age, 1.2 years; range, 0.4–12.3 years) were reviewed. Mitral valve geometry was evaluated by measuring coaptation depth using echocardiographic apical four-chamber views at the initial presentation. Patients were dichotomised according to the mitral regurgitation severity: patients with moderate or severe secondary mitral regurgitation (n=6) and those with mild secondary mitral regurgitation (n=10). A total of 58 healthy children were considered as normal controls, and a regression equation to predict coaptation depth by body surface area was derived: coaptation depth [mm]=4.37+1.34×ln (body surface area [m 2 ]) (residual standard error, 0.49; adjusted R 2, 0.68; p<0.0001). Compared with patients with mild secondary mitral regurgitation, those with moderate or severe secondary mitral regurgitation had significantly larger coaptation depth z-scores (6.4±2.3 versus 1.9±1.4, p<0.005), larger mitral annulus diameter z-scores (3.6±2.6 versus 0.9±1.8, p<0.05), higher left ventricular sphericity index (0.89±0.07 versus 0.79±0.06, p<0.005), and greater left ventricular fraction shortening (0.15±0.05 versus 0.09±0.05, p<0.05). In conclusion, geometric alteration in the mitral valve and the left ventricle is associated with the severity of secondary mitral regurgitation in paediatric dilated cardiomyopathy, which would provide a theoretical background to surgical intervention for secondary mitral regurgitation in paediatric populations.